Brazilian law for the inclusion of people with disabilities: changes in the civil code and social achievements (Research, Society and Development, 2022)
The history of people with disabilities in Brazil, as with several civilizations in the world, was marked by an initial phase of elimination and exclusion, leaving this segment on the margins of society, historically perceived as incapable or sick people, thus the present research, seeks to understand and interpret the main changes made to the Civil Code of 2002 and the social achievements of people with disabilities with the advent of the Brazilian Inclusion Law. As a method of approach, the deductive was used, since the research starts from the analysis of Law 13.146 / 2015 (Brazilian Law of Inclusion); specifying by the changes in the Civil Code of 2002, mainly in the capacities and disabilities institute. In the research techniques regarding the procedure, the historical method was used, the important moments in the history of the person with disabilities and their social achievements were reported. In addition to this, the monograph was applied where people with disabilities were studied in some depth. As a result, the importance of the rules in the legal system was realized, allowing the protection of the demands of this part of society to happen. In Brazil, Law 13,146 / 2015, the Brazilian Inclusion Law, constitutes a landmark in the regulation of the rights and guarantees of this population. In the analysis of the modifications of the Civil Code, it was observed that the theory of capacities and disabilities was changed, aiming at the recognition of the person with disabilities as capable of exercising rights and duties in the civil order, who now have the capacity to contract marriage; participate in business and decide on issues of interest.